Crowdfunding as an Innovative Mechanism for Financing Start-Ups– The Ninvesti and TwiizaPlatforms as a Model - Dabah, Mohamed Ridha; Benbraika , Abdelouahab (Milev Journal of Research and Studies, 2021)
This study aims to clarify the role of crowdfunding as a modern technique for financing startups, and in order to identify the importance of this technique; we reviewed both the conceptual framework of startups and crowdfunding with and to identify the platforms of Twiiza and Ninvesti. The results of this study concluded that there are many financing difficulties that startups face in Algeria, which is why and this is why crowdfunding is considered one of the best financing alternatives on which we can count, but we see that this type of funding is still fairly recent in Algeria, where it has not yet been found. The financial and entrepreneurial culture necessary for its development, and this manifests itself through the lack of crowdfunding platforms on the one hand, as well as the weakness observed in the activities of crowdfunding platforms on the other hand, and this is why Algeria must redouble its efforts to promote crowdfunding by benefiting from the experiences of leading countries in terms of financing and by benefiting from emerging institutions.